Obnova kláštera ve Šternberku - Janečková, Klára (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Zadáním diplomové práce bylo vypracování architektonické studie obnovy bývalého augustiniánského kláštera ve Šternberku a kompoziční řešení přilehlého areálu. Klášter je od roku 1993 ve vlastnictví města Šternberk, které se snaží o jeho postupnou revitalizaci. Cílem návrhu je šetrné využití stávající budovy a zpřístupnění přilehlé klášterní zahrady veřejnosti. V reakci na požadavky investora a koexistenci kostela byla v objektu navržena základní umělecká škola, restaurace, vinárna, hotel, obřadní síň a výstavní prostory. Vnitřní atrium bylo zastřešeno a doplněno o výtah se schodištěm. V návaznosti na navrhované funkční využití a nevyhovující průjezd do areálu bylo do západní části umístěno podzemní parkoviště s možností průjezdu na předklášterní nádvoří. Do zahrady byly vytvořeny dva nové vstupy z ulic Opavská a Zahradní.

The task of the diploma thesis was the development of an architectural study of the restoration of the former Augustinian monastery in Šternberk city and the compositional layout of the adjacent area. Since 1993, the monastery has been owned by the Šternberk municipality, which is trying to gradually revitalize it. The goal of the proposal is to carefully use the existing building and make the monastery garden accessible to the public. In response to the demands of the investor and the coexistence of the church, a primary art school, restaurant, wine bar, hotel, ceremony hall and exhibition spaces were designed in the building. The inner atrium was covered by glass roof and completed with an elevator and stairs. In connection with the proposed functional use and due to inadequate access to the premises, an underground parking lot was placed in the western part with the possibility of entry to the courtyard in front of monastery. Two new entrances were created to the garden, connecting Opavská street with Zahradní street.
Restoration of the monastery in Šternberk
Keywords: Šternberk; klášter; obnova; skleněná střecha; atrium; vinárna; restaurace; základní umělecká škola; hotel; zahrada; podzemní parkování; Šternberk; monastery; restoration; glass roof; atrium; wine bar; restaurant; primary art school; hotel; garden; underground parking